2010
DOI: 10.4314/swj.v5i1.61485
|View full text |Cite
|
Sign up to set email alerts
|

<i>Schistosoma mansoni</i> infections amongst school children in Jos, Nigeria.

Abstract: A parasitological study of intestinal schistosomiasis among public/private primary and secondary school pupils in Jos North Local Government Area of Plateau State, Nigeria was conducted. Out of the 280 stool samples examined, 13(4.6%) were positive for S. mansoni parasites. Single, dual and multiple parasitic infections were recovered. The study provided some data on infections with intestinal parasites among the pupils/students in Jos, Nigeria, recommending that control and treatment of these infections is of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 8 publications
4
9
4
Order By: Relevance
“…Infection with Schistosomes were found to be higher among students of the age group 19-22 years with 7.2%, followed by 16-18 years with 6.0% and 13-15 years with 4.0% as shown in Table 2.The result reveals that as age increases the infection rate increases there by showing a significant differences between age and the prevalence of the infection (p < 0.05).This findings agrees with Agere et al (2010) in Jalingo and Biu et al (2009). It disagrees with the findings of Damen et al (2006) and Goselle et al (2010) who reported a decrease in prevalence with increase in age. The increase in the infection rate in this study as age increases may be attributed to more contaminated water contact over time among the students as the engage in activities such as irrigation farming, fishing and swimming.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Infection with Schistosomes were found to be higher among students of the age group 19-22 years with 7.2%, followed by 16-18 years with 6.0% and 13-15 years with 4.0% as shown in Table 2.The result reveals that as age increases the infection rate increases there by showing a significant differences between age and the prevalence of the infection (p < 0.05).This findings agrees with Agere et al (2010) in Jalingo and Biu et al (2009). It disagrees with the findings of Damen et al (2006) and Goselle et al (2010) who reported a decrease in prevalence with increase in age. The increase in the infection rate in this study as age increases may be attributed to more contaminated water contact over time among the students as the engage in activities such as irrigation farming, fishing and swimming.…”
Section: Discussioncontrasting
confidence: 99%
“…This study also revealed a statistically significant higher prevalence in males compared to the females which agrees with the findings of Damen et al (2006); Biu et al (2009); Goselle et al (2010). The males often engaged in activities such as swimming, fishing, and irrigation especially during holidays or during their outing days more than their female counterpart.…”
Section: Discussionsupporting
confidence: 91%
“…A prevalence of T. trichiura 14% was recorded in the present research which corresponds with the low prevalence 7.5% and 3.2% reported by Osazuwa et al, and Ekpenyong et al, (2008) respectively, but disagrees with the research of Wosu and Onyeabor who reported 34.5%. Least prevalent in our study is S. mansoni (4.4%), which agrees with a study on primary school level, 6(4.29%) and secondary school 7(5.00%) by Goselle et al, (2010).…”
Section: Resultssupporting
confidence: 82%
“…14.4% from Brazil [31], 4.6% from Jos Nigeria [32], 12.6% from Agaie Niger state Nigeria [33], and 19.8% from Ghana [34]. This difference may be because of ecological variation, Climatic condition of study area, sample size used, contact with open water sources which is infested with infective stage of the parasites and presence of intermediate in water bodies in the area.…”
Section: Discussionmentioning
confidence: 99%